Pengaruh Mobilisasi Dini Ibu Post Partum Terhadap Penurunan Tinggi Fundus Uteri - Eni Susanti; Dyah Esti P (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Normally uterus begins to wane after bornplacenta, usually at 1-2 fingers under navel.However, of 8 mother who have born spontan havenormal decrease uterine fundus height while 5 theother people at 7 days have late decrease uterinefundus height. The goal of this reseach is to analysiseffect of early mobilization post partum mother todecrease uterine fundus height in the health centerof lepele district camplong robatal regency.Thisresearch uses analytic method and reseach designuses retrospektiv. The population are post partummothers at first time until 5 days on Agustus –September 2014 taking 32 women. Sample whichtaken 30 respondents who are taken probabilitySampling with simple random sampling. Theindependent variable is early mobilization anddependent variable is decrease uterine fundusheight. The collect of data using observation that beprocessed using cross tabulation and spearman ranktest. The result were obtained almost half motherpost partum do enough early mobilization as muchas 11 people and almost half mother post partumhave enough decrease uterine fundus height asmuch as 13 people. According statistick testspearman rank is gotten ρ<α (0,000<0,05) so Ho isrefuse and Ha is receive so there are effect of earlymobilization post partum mother to decrease uterinefundus height in the health center of lepele districtcamplong robatal regency. Expected from this research to improve toimprove the giving of conseling, information andeducation (KIE) to mother, husband and family andalso as materials and professional framework forhealth personnel for giving couseling to post partummother.